A place for us [large type] : a novel - Mirza, Fatima Farheen, 1991- (Thorndike Press, a part of Gale, a Cengage Company, 2018)
"The first novel from Sarah Jessica Parker's new imprint, SJP for Hogarth, A Place for Us is a deeply moving and resonant story of love, identity and belonging. A Place for Us unfolds the lives of an Indian-American Muslim family, gathered together in their Californian hometown to celebrate the eldest daughter, Hadia's, wedding - a match of love rather than tradition. It is here, on this momentous day, that Amar, the youngest of the siblings, reunites with his family for the first time in three years. Rafiq and Layla must now contend with the choices and betrayals that lead to their son's estrangement - the reckoning of parents who strove to pass on their cultures and traditions to their children; and of children who in turn struggle to balance authenticity in themselves with loyalty to the home they came from. In a narrative that spans decades and sees family life through the eyes of each member, A Place For Us charts the crucial moments in the family's past, from the bonds that bring them together to the differences that pull them apart. And as siblings Hadia, Huda, and Amar attempt to carve out a life for themselves, they must reconcile their present culture with their parent's faith, to tread a path between the old world and the new, and learn how the smallest decisions can lead to the deepest of betrayals. A deeply affecting and resonant story, A Place for Us is truly a book for our times: a moving portrait of what it means to be an American family today, a novel of love, identity and belonging that eloquently examines what it means to be both American and Muslim -- and announces Fatima Farheen Mirza as a major new literary talent. "--